Legal Sanction for Non-observance of Expediency in Power of Attorney - Ã˜ÂÃ˜Â§Ã˜Â¬Ã›ÂŒ Ã˜Â¹Ã˜Â²Ã›ÂŒÃ˜Â²Ã›ÂŒ, Ã˜Â¨Ã›ÂŒÃšÂ˜Ã™Â†; Ã˜Â§Ã˜Â¹Ã˜ÂªÃ™Â…Ã˜Â§Ã˜Â¯, Ã™Â…Ã˜Â±Ã›ÂŒÃ™Â… (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Power of attorney (PA) contract is among the specified contracts that are widely used in society and peopleâs legal relations, because on one hand, people are not compelled to directly vindicate their rights and, on the other hand, the above-mentioned contract is of high importance in lawsuits and restoring the victimâs rights in courts of law. Through signing contract of PA, the attorney and the client reciprocate obligation and right and hold judicial relations and mutual commitments and responsibilities. Among these commitments is the observance of the clientâs expediency. Since this commitment overshadows other commitments of the attorney and is somehow regarded as the foundation of all his commitments, it is of special importance. Despite the assertion on the above-mentioned commitment in article 667 of the civil law, the legal sanction for its violation in various obligations is ambiguous. Silence of the law, weakness of the writings, and being involved in this issue has made us search for an answer whose summary is as follows: the legal actions that have been carried out without observing the clientâs expediency is regarded as effective â except for the obligation in which the client has connived with the party of contract â although, in case of availability of options, the clients can remove loss from themselves.